Study of the biologically active acyclic ureas by nuclear magnetic resonance - Bakibaev, А.А.; Sadvakassova, М.Zh.; Malkov, V.S.; Еrkasov, R.Sh.; Sorvanov, A.A.; Kotelnikov, O.A. (KU publ., 2020)
A wide variety of acyclic ureas comprising alkyl, arylalkyl, acyl, and aryl functional groups are investigated by nuclear magnetic resonance spectroscopy. In general, spectral characteristics of more than 130 substances based on acyclic ureas dissolved in deuterated dimethyl sulfoxide at room temperature are studied. The results obtained based on the studies of 1H and 13C NMR spectra of urea and its N-alkyl-, N-arylalkyl-, N-aryland 1,3-diaryl derivatives are presented, and the effect of these functional groups on the chemical shifts in carbonyl and amide moieties in acyclic urea derivatives is discussed. An introduction of any type of substituent (electron-withdrawing or electron-donating) into urea molecule is stated to result in a strong upfield shift in 13C NMR spectra relatively to unsubstituted urea. A strong sensitivity of NH protons to the presence of acyl and aryl groups in nuclear magnetic resonance spectra is pointed out. In some cases, qualitative dependencies between the chemical shifts in the NMR spectra and the structure of the studied acyclic ureas are revealed. A summary of the results on chemical shifts in the NMR spectra of the investigated substances allows determining the ranges of chemical shift variations of the key protons and carbon atoms in acyclic ureas. The literature describing the synthesis procedures are provided. The results obtained significantly expand the methods of reliable identification of biologically active acyclic ureas and their metabolites that makes it promising to use NMR spectroscopy both in biochemistry and in clinical practice.
Ядролық магниттік резонанс əдісімен биологиялық белсенді ациклдік мочевиналарды зерттеу
Исследование биологически активных ациклических мочевин методом ядерного магнитного резонанса
Keywords: urea; alkylurea; arylurea; acylurea; diarylurea; urea fragment; amide group; NMR spectroscopy; chemical shift